2008
DOI: 10.1128/jcm.02033-07
|View full text |Cite|
|
Sign up to set email alerts
|

Timing of Specimen Collection for Blood Cultures from Febrile Patients with Bacteremia

Abstract: Bloodstream infections are an important cause of morbidity and mortality. Physician orders for blood cultures often specify that blood specimens be collected at or around the time of a temperature elevation, presumably as a means of enhancing the likelihood of detecting significant bacteremia. In a multicenter study, which utilized retrospective patient chart reviews as a means of collecting data, we evaluated the timing of blood culture collection in relation to temperature elevations in 1,436 patients with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 31 publications
2
48
1
5
Order By: Relevance
“…A retrospective, multicenter study of 1,436 adult patients found no significant association between enhanced recovery of bacteria and collection of blood cultures at the time of fever spike. The authors concluded that, at least in the adult population, the timing of blood culture collection is not important and should be based on convenience (24). This coincides with IDSA/ASM guidelines that collection should be dictated based on the patient's acuity (22).…”
Section: Blood Culture Collectionmentioning
confidence: 99%
“…Current guidelines advocate 2-3 sets obtained simultaneously from different venipunctures or serially within 0-24 hours for optimal detection of bacteremia and interpretation of blood culture results [1][2][3][4][5]. The potential benefits of multiple sets include better detection of bacteremia, distinguishing contaminants and the recognition of persistent bacteremia [4].…”
Section: Introductionmentioning
confidence: 99%